The Benefit of Dexmedetomidine on Postoperative Cognitive Function Is Unrelated to the Modulation on Peripheral Inflammation: A Single-center, Prospective, Randomized Study. Issue 2 (February 2020) - Mei, Bin; Xu, Guanghong; Han, Wei; Lu, Xiaolong; Liu, Ruihong; Cheng, Xinqi; Chen, Shishou; Gu, Erwei; Liu, Xuesheng; Zhang, Ye
Abstract : Background: Dexmedetomidine potentially confers an advantage to reduce the incidence of postoperative delirium (POD) in surgical patients. Anti-inflammation is important effect of this sedative drug. In this study, we aimed to investigate whether the effect of dexmedetomidine on the postoperative cognitive function is via inhibiting peripheral inflammation. Methods: A prospective, randomized, controlled study was conducted with patients 65 years of age or above who received total knee arthroplasty from January 2019 to May 2019. The patients were randomly assigned to receive spinal anesthesia supplemented with propofol or dexmedetomidine for sedation. The incidence of POD was the primary endpoint and was evaluated with the Confusion Assessment Method, and incidence of postoperative cognitive dysfunction was assessed with the Mini-Mental State Examination. Blood samples were collected postoperatively to test the plasma concentrations of interleukin-6, tumor necrosis factor-α, and S100β. Results: A total of 366 patients were randomly assigned to 2 groups. Patients who received dexmedetomidine sedation had lower incidences of POD and better postoperative cognitive function than patients sedated with propofol. There was no difference in postoperative plasma concentrations of tumor necrosis factor-α and interleukin-6 between the 2 groups. The concentration of S100β 48 hours after surgery was higher in patients sedated with propofol than in patients who received dexmedetomidine sedation. Conclusion: Intraoperative sedation with dexmedetomidine conferred better postoperative neurocognitive function for elderly patients who received total knee arthroplasty. This effect was unrelated to the modulation of dexmedetomidine on peripheral inflammation.